Jogo de tabuleiro sobre o sistema articular em sala de aula invertida: ferramenta para o ensino de anatomia - Pinho, Francisco Alves de (2022)
The use of active methodologies holds methods that place the student as the center in the teaching and learning process, while the teacher stands out as a mediator and facilitator of learning. In this context, among these methodologies we have the flipped classroom and board games, which are important tools in the anatomy teaching process in universities in the health area. Based on these premises, the objective of this research was to verify the application of the use of a board game in the teaching practice of the articular system, in the inverted classroom, in the discipline of human anatomy. A descriptive, quasi-experimental study with a quantitative approach was carried out. A board game with 54 cards was constructed, validated, and applied to evaluate learning. Initially, the inverted classroom methodology was used, where all the necessary material was made available to the students for previous study of the content related to the articular system before the face-to-face meeting. To play the game, the groups were divided, using probability as a tool. The study participants were evaluated before, after, and six months after the game was played. To validate the content and appearance of all the educational material, expert judges in the field of anatomy and pedagogy were invited to participate. They validated the material, obtaining an overall CVI of 0.94. Statistically significant differences in learning were observed after using the board game (p< 0.1). It was found that the board game when compared to traditional teaching promotes significant learning. Regarding long-term learning (after 6 months), there was retention of knowledge by students with the use of the game (p< 0.01) when compared to the traditional group. Regarding the evaluation of the board game by the participants, the game was well accepted and indicated for use in future classes. The participation, motivation, and engagement of the students and, finally, a collaborative spirit were also noticeable, as it took on a playful and educational form during the entire process of applying the game in the classroom. Therefore, we conclude that the use of the board game in an inverted classroom promotes short and long-term learning for the students, being an essential tool in the teaching and learning process.